Thymol Production from Callus Culture of Nigella sativa L. - Al-Ani, Nabeel K. (Plant Tissue Culture and Biotechnology, 2009)
Roots, hypocotyls and leaves of Nigella sativa L. were collected from the seedlings raised on sterilized filter paper and cultured on MS supplemented with different concentrations of 2,4-D (0.0, 1.0, 2.0, 3.0, 4.0 mg/l) and Kn (0.0, 1.0, 1.5, 2.0, 2.5, 3.0, 5.0). The best callus production was obtained from leaf explants with 1 mg/l 2,4-D and 1.5 mg/l Kn. The higher thymol concentrations were extracted after 75 days for the above callus; which was detected by HPLC using retention time. This is the first report in Iraq about extracting thymol from callus of Nigella sativa. Key words: Thymol produiction, Callus culture, Nigella sativa D. O.I. .3329/ptcb.v18i2.3649 Plant Tissue Cult. & Biotech. 18(2): 181-185, 2008 (December)